EFFECTS OF SCAFFOLDING ON STUDENTS’ EXTRANEOUS COGNITIVE LOAD IN THE DEEP LEARNING APPROACH - Eri Hasna Safira; Ismail Fikri Natadiwijaya (Journal International Inspire Education Technology, 2025)
This study explores how scaffolding, when blended with a deep learning approach, can ease students’ extraneous cognitive load during junior high school science lessons. A quasi-experimental Nonequivalent Control Group Design was used because the research took place in real classroom settings, where random assignment was not possible. To reduce potential selection bias, both classes were matched based on prior science achievement and taught by the same teacher using comparable learning materials. A total of 62 seventh-grade students participated, with 31 in the experimental group and 31 in the control group. In the experimental class, scaffolding was implemented through step-by-step guidance, worked examples, prompts, and gradually reduced support as students progressed through deep learning activities such as exploring problems, connecting concepts, and reflecting on their thinking. Data were collected using an Extraneous Cognitive Load Questionnaire adapted from Paas, van Merriënboer, and Sweller (2021) and analyzed with an Independent Samples t-test. The findings revealed a significant difference between the two groups, t(60) = 9.03, p < .001, with the experimental class (M = 2.52) reporting a substantially lower cognitive load than the control class (M = 4.41). The 1.89-point decrease reflects a meaningful practical improvement, showing that students experienced less unnecessary mental effort while engaging with complex material. Overall, the study shows that combining scaffolding with deep learning strategies not only strengthens students’ understanding but also makes the learning process mentally more manageable, leading to a more effective and engaging science learning experience.